Research on the Parametric Design Method of Torque Converters of the Heavy-duty Hydraulic Automatic Transmission - Li Zhengwei; Wu Huaichao; Nie Long; Pan Keqiang; Lu Fang; Chen Xingyan (Jixie chuandong)
At present, the demand for heavy-duty hydraulic automatic transmission in engineering machinery and other equipment is increasing. As one of the core components of such kind of transmission, the design of hydraulic torque converters requires better accuracy and efficiency. Due to the difference of scale and torque, the design method of common torque converters is no longer applicable. The torque converter parametric design process is separated from the 3D software model generation process currently, which prolongs the design cycle. Therefore, this study presents a parametric design method for torque converters of the heavy-duty hydraulic automatic transmission and develops the parametric design software. Firstly, the geometric model of torus is established by constructing the middle streamline by two elliptical arcs, the camber line is designed with the quartic B-spline curve, and a method of controlling the shape of the camber line through the two-level inlet and outlet angles and vertex coordinates is proposed. The connection is established between the blade camber line shape control method and the curve control points, and the constraint conditions of camber line control parameters are designed. The automatic design program of torque converters is developed based on the NX Open software, and the central scheduling data processing framework is established with parameter rationality checking as the constraints. The instance results show that the design method can make the torque converter get reasonable shape quickly.